PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS SCIENTIFIC APPROACH UNTUK MEMBANGUN KARAKTER KEPEDULIAN DAN KEDISIPLINAN - Veryliana Purnamasari; Muhammad Nur Wangid (Jurnal Pendidikan Karakter, 2016)
Abstrak: Penelitian ini bertujuan menghasilkan perangkat pembelajaran berbasis scientific approachKeindahan Alam Negeriku yang layak bagi kelas IV SD untuk membangun karakter kepedulian dankedisiplinan dan mengetahui keefektifannya. Penelitian ini merupakan penelitian dan  pengembanganyang mengacu pada model Borg Gall. Subjek uji coba siswa kelas IV SDN Salamrejo Sentolo, KulonProgo. Subjek uji coba awal terdiri atas 4 siswa. Subjek uji coba lapangan terdiri atas 10 siswa yangbelum terlibat dalam uji coba awal, dan subjek uji lapangan operasional terdiri atas 39 siswa dari kelasIVA dan kelas IVB. Hasil penelitian berupa perangkat pembelajaran yang meliputi: silabus, RPP, LKS,dan instrumen penilaian. Hasilnya menunjukkan perangkat pembelajaran yang telah dikembangkanlayak menurut ahli materi dan ahli pembelajaran dengan kategori penilaian sangat baik. Perangkat pembelajaran dinilai efektif karena hasil uji t pada karakter peduli sebesar 4,854 dan karakter disiplinsebesar 1,926 lebih besar dari t table yaitu 1,684 sehingga menunjukkan ada perbedaan yang signifikanterhadapkarakterdisiplindanpeduliantarasiswayangmengikutipembelajarantanpaperangkatpembelajarandanyangmenggunakanperangkatpembelajaranhasilpengembangan.Kata Kunci: pengembangan, perangkat pembelajaran, scientific approach, karakter LEARNING SOFTWARE DEVELOPMENT BASED ON SCIENTIFIC APPROACH TO BUILD CHARACTER OF CARE AND DISCIPLINE Abstract: This study aims to (1) produce a learning device based on scientific approach that can befeasible to develop the character of elementary school fourth graders especially caring and disciplinecharacter and (2) determine the effectiveness of learning device based on scientific approach that candevelop the character of elementary school fourth graders especially caring and discipline character.This was a research and development (R D) study consisting of ten stages, namely: (1) preliminarystudy and data collection, (2) planning, (3) product draft development, (4) preliminary field tryout, (5)revision of the tryout result, (6) field tryout, (7) product finalization based on the field tryout result, (8)operational field testing, (9) final product finalization and (10) dissemination and implementation. Thetryout subjects were Grade IV students of SDN Salamrejo Sentolo Kulon Progo. The preliminary fieldtryout subjects consisted of four students. The main field testing subjects consisted of ten studentswho were not involved in the preliminary field tryout. The operational field tryout subjects consistedof 39 students from Grade IV A and Grade IV B.The result of this research is a learning device consistingofasyllabus,lesson plans, student worksheets, and assessment instruments. The resultsof expertshowthatthelearningdevicehasbeendevelopedisfeasibleaccordingtothematerialexpertandlearningexpertwithexcellentassessmentcategory.Thedeviceisalsoconsideredaneffectivelearningbecausethe results of the t test on the character of caring are 4.854, in the character of the discipline1.926 which greater than t table is 1.684 indicating significant difference of the character of disciplineand care among the students who follow the teaching and learning and those without using learningdevice. Keywords: development, learning device, scientific approach, characters